Early blood pH as an independent predictor of neurological outcome in patients with out-of-hospital cardiac arrest: A retrospective observational study. Issue 17 (30th April 2021) - Lin, Chin-Han; Yu, Shao-Hua; Chen, Chih-Yu; Huang, Fen-Wei; Chen, Wei-Kung; Shih, Hong-Mo
Abstract : Abstract: Metabolic acidosis is observed in 98% of patients with out-of-hospital cardiac arrest (OHCA). The longer the no-flow or low-flow duration, the more severe is the acidosis in these patients. This study explored whether blood pH in early stages of advanced life support (ALS) was an independent predictor of neurological prognosis in patients with OHCA. We retrospectively enrolled patients with OHCA from January 2012 to June 2018 in a single-medical tertiary hospital in Taiwan. Patients with OHCA whose blood gas analyses within 5 minutes after receiving ALS at the emergency department (ED) were enrolled. Patients younger than 20 years old, with cardiac arrest resulting from traumatic or circumstantial causes, with return of spontaneous circulation (ROSC) before ED arrival, lacking record of initial blood gas analysis, and with do-not-resuscitate orders were excluded. The primary outcome of this study was neurological status at hospital discharge. In total, 2034 patients with OHCA were enrolled. The majority were male (61.89%), and the average age was 67.8 ± 17.0 years. Witnessed OHCA was noted in 571 cases, cardiopulmonary resuscitation was performed before paramedic arrival in 512 (25.2%) cases, and a shockable rhythm was observed in 269 (13.2%). Blood pH from initial blood gas analysis remained an independent predictor of neurological outcome after multivariate regression. Blood pH at early stages of ALS was an independent prognostic factor of post-OHCA neurological outcome. Blood gas analysis on arrival at the ED may provide additional information about the prognosis of patients with OHCA.